Enhancing STEM Education through IoT-Based Distance Monitoring Projects in High Schools - Istiqomah Istiqomah; Khilda Afifah; Porman Pangaribuan; Teguh Patriananda; Ni Kadek Cindy Sriastiti; Justin Fairman Tan; Tsania Puspa Kirana; Garry Nelson (Smart Society, 2026)
This community service program was conducted in response to the demands of the Fourth Industrial Revolution, which requires stronger digital literacy and practical STEM competencies in schools. The program aimed to introduce IoT-based STEM learning to teachers and students at Situraja State Senior High School (SMAN Situraja), a rural school in West Java, Indonesia, to enhance digital literacy and promote hands-on STEM education. To achieve this, the program implemented an IoT-based distance monitoring project using an ultrasonic sensor, an ESP32 microcontroller, and the Blynk platform through a project-based learning approach that included lectures, collaborative practical sessions, and interactive feedback activities. The program was evaluated using post-activity questionnaires administered to both teachers and students to capture their perceptions of the learning activities and outcomes. The results showed highly positive teacher responses, with 75–100% of participants selecting "strongly agre across all evaluation items, including 100% agreement on understanding IoT data transmission and the relevance of STEM integration. Student feedback also indicated positive motivation toward STEM learning, with 48% of students strongly agreeing that the activity increased their interest in STEM. However, student responses related to physics concept understanding and real-world application were more varied, with up to 48% selecting neutral responses in these areas. This difference suggests that teachers more readily recognized the instructional relevance of the program, while some students were still adapting to newly introduced IoT and physics concepts.